Mannu and the jamun thief - Radhika chadha; Priya kuriyan (Chennai : Tulika Publishers, 2021)
Mannu the monkey has been waiting for this day - when the pulply - shurply jamun are pulply - shulpy ripe.
pictures Priya kuriyan
Keywords: Childrens story; story of jammun